If-(x-1)=5

Simple and best practice solution for If-(x-1)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for If-(x-1)=5 equation:


Simplifying
If + -1(x + -1) = 5

Reorder the terms:
fI + -1(-1 + x) = 5
fI + (-1 * -1 + x * -1) = 5
fI + (1 + -1x) = 5

Reorder the terms:
1 + fI + -1x = 5

Solving
1 + fI + -1x = 5

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + fI + -1 + -1x = 5 + -1

Reorder the terms:
1 + -1 + fI + -1x = 5 + -1

Combine like terms: 1 + -1 = 0
0 + fI + -1x = 5 + -1
fI + -1x = 5 + -1

Combine like terms: 5 + -1 = 4
fI + -1x = 4

Add 'x' to each side of the equation.
fI + -1x + x = 4 + x

Combine like terms: -1x + x = 0
fI + 0 = 4 + x
fI = 4 + x

Divide each side by 'I'.
f = 4I-1 + xI-1

Simplifying
f = 4I-1 + xI-1

See similar equations:

| (3.2)x(0.64)= | | (x*5.25)/4.8=214 | | 1x+12=4 | | (x*6)/4.8=214 | | 175+0.1h=125+0.25h | | (x*6)/0.8=214 | | (3)-3(-2)= | | 5a+3-2a=-7 | | 7(x+1)-(4x-5)=2 | | 3x^2+11.5x=2 | | -3(3x-3)= | | 2y+6=13y-49 | | (x*6)/6=220 | | -4(-2v+3)-2v=2(v-1)-8 | | 3x-12=6x-12+3x | | -3(x-1)-2(4-8x)=2-(x+1) | | 14=(8X+12) | | 4x=3-7 | | 5=34 | | 10x-50=-70 | | 2S-7=-7 | | -3*5=x | | 3/4-1/3=1/4 | | 4.5x+3-2x=8 | | -0.5d+2=-4(d-0.5) | | 4*(ab)= | | 3(m-5)=4(1-4m) | | 198-24=6x | | -3x5= | | 0.4x-10=-14 | | 4(x−7)=8x−12 | | 7(w+4)=-5(2w-6)+9w |

Equations solver categories